Auctions with Endogenous Participation and Quality Thresholds : Evidence from ODA Infrastructure Procurement - Estache, Antonio; Iimi, Atsushi (2012)
Infrastructure projects are often technically complicated and highly customized. Therefore, procurement competition tends to be limited. Competition is the single most important factor toward auction efficiency and anti-corruption. However, the degree of competition realized is closely related to bidders' entry decision and the auctioneer's decision on how to assess technical attributes in the bid evaluation process. This paper estimates the interactive effects among quality, entry, and competition. With data on procurement auctions for electricity projects in developing countries, it is found that large electricity works are by nature costly and can attract only a few participants. The limited competition would raise government procurement costs. In addition, high technical requirements are likely to be imposed for these large-scale projects, which will in turn add extra costs for the better quality of works and further limit bidder participation. The evidence suggests that quality is of particular importance in large infrastructure projects and auctioneers cannot easily substitute price for quality.